Effect of Heat Treatment on Low‐Cycle Fatigue Performance of LZ91 Mg–Li Alloy. Issue 9 (6th August 2021) - Li, Yang; Lu, Zhengtong; Liu, Shuhao; Li, Dalei; Zou, Yun
Abstract : Herein, the effects of heat treatment on the microstructure, tensile properties, and low‐cycle fatigue properties of the LZ91 Mg–Li alloy are investigated. The results indicate that after heat treatment, the α‐phase undergoes spheroidization, and a portion of the needle‐like α‐phase is distributed at the β‐phase grain boundary; in addition, the ultimate tensile strength (UTS) and elongation of the material increase by 9.6% and 20%, respectively, and the low‐cycle fatigue life is improved. The increase in the UTS of the specimen is attributed to the precipitation of the needle‐like α‐phase, whereas that in material plasticity is attributed to α‐phase spheroidization after heat treatment. It is observed that fatigue cracks all originate on the surface of the specimens, predominantly in the β‐phase. The needle‐like α‐phase suppresses the initiation of macro fatigue cracks, and the increased α‐phase microhardness decelerates the crack growth rate, thereby improving the low‐cycle fatigue life of the alloy. Abstract : After heat treatment, the α‐phase undergoes spheroidization, and some needle‐like α‐phase is distributed at the β‐phase grain boundary in the LZ91 Mg–Li alloy. The needle‐like α‐phase suppresses the initiation of macro fatigue cracks, and the increased α‐phase microhardness decelerates the crack growth rate, thereby improving the low‐cycle fatigue life of the alloy.